A new species of Epidendrum (Orchidaceae: Laeliinae) of the Incomptum group from the north of Antioquia, Colombia - Rincón González, Milton; Santiago Ayala, Elizabeth 1973-; Hágsater Gartenberg Eric 1945-; Vieira Uribe, Sebastián (2024)
A new species of Epidendrum of the Incomptum group is described and illustrated, thus far found only at the type locality. Information is provided to separate the species belonging to the Arbuscula and Incomptum groups. Additionally, the new taxon described herein, Epidendrum pembertonii, is thoroughly compared with the four most morphologically similar species (E. brenesii, E. bisulcatum, E. foldatsii, E. sotoanum), revealing notable differences in the number and shape of leaves, inflorescence length, flower color, venation of sepals, as well as the shape and ornamentation of the lip and column.
Se describe e ilustra una especie nueva de Epidendrum del grupo Incomptum, hasta ahora encon-trada solamente de la localidad tipo. Se proporciona información para separar las especies pertenecientes a los grupos Arbuscula e Incomptum. Además, el nuevo taxón descrito aquí, Epidendrum pembertonii, se compara minuciosamente con las cuatro especies morfológicamente más similares (E. brenesii, E. bisulcatum, E. foldatsii, E. sotoanum), mostrando diferencias notables en la cantidad y forma de las hojas, longitud de la inflorescencia, color de las flores, venación de los sépalos, forma y ornamentación del labelo y columna.
Keywords: LAELIINAE -- IDENTIFICACIÓN -- ANTIOQUÍA (COLOMBIA); ESPECIES -- IDENTIFICACIÓN -- ANTIOQUÍA (COLOMBIA); ORQUÍDEAS -- CLASIFICACION